(untitled) (Stavební obzor - Civil Engineering Journal, 2022)
In recent years, there have been cases of strengthening bridge structures with polyurethane cement mortar. To further explore the properties of polyurethane materials, the effects of emery, lime, quartz sand and cement on the mechanical properties of polyurethane powder composites are studied by three-point flexural test. In the flexural test, the polyurethane cement composite formed a control group by changing the content of polyester polyol. The flexural strength and ductility are improved to a certain extent due to the addition of polyester polyol.The average flexural strength of other polyurethane powder composites such as polyurethane emery test block is 45.1 MPa and the corresponding strain is 6203 με, the average flexural strength of polyurethane lime test block is 33.4 MPa and the corresponding strain is 6470 με, the average flexural strength of polyurethane quartz sand test block is 49.23 MPa and the corresponding strain is 7521 με. The results show that the flexural strength of polyurethane emery material and polyurethane quartz sand material is higher than that of polyurethane cement, which can be used to replace cement to a certain extent to reduce the cost of polyurethane composite material.